Pemberdayaan Masyarakat Melalui Pengelolaan Limbah Cangkang Telur Ayam Menjadi Pupuk Organik Di Desa Gitik Kecamatan Rogojampi Kabupaten Banyuwangi - Cindy Selya Maharani; Cindy Ernanda Putri; Ahmad Qossam Saifullah; Dendi Kurniaji; Putri Dwi Pratiwi; M. Bima Riyanto; Rido Febrian; Sefri Ton; Dani Agung Wicaksono (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Egg shells, chicken bones and beef bones are included in organic waste. According to Rahmayanti (2020), organic waste comes from living creatures which can be reused into organic fertilizer. The high phosphorus content in egg shells is 95% and the high nitrogen content in livestock bones is able to fulfill plant elements for growth and development. This research is in line with research by Lubis, et al., (2020), where the content of egg shells has a significant effect on increasing the height growth of Japanese Cambodian (Adenium obesum) starting from increasing plant height and increasing the number of plant leaves. On the other hand, the use of organic fertilizer from chicken, beef and egg shell waste can be an alternative in controlling environmental problems.